High school musical 2 [videorecording (DVD)] - Ortega, Kenny; Efron, Zac; Hudgens, Vanessa, 1988-; Tisdale, Ashley, 1985- (Distributed by Walt Disney Studios Home Entertainment, 2007)
For Troy, Gabriella, Chad, and Taylor, summer vacation is no day at the beach. Thanks to Troy, they are all working at a country club founded by Ryan and Sharpay's family. The club's annual talent show is right around the corner and Sharpay's competitive instincts are sizzling. She dumps Ryan as her singing partner and starts wooing Troy to join her onstage instead. Gabriella is not very happy that Tony agreed to sing with Sharpay, instead of her. Things heat up on the laws of high society. Now Troy has to decide between receiving a potential scholarship and making things right with Gabriella and his friends.